Conduct of dental missions by the Philippine Dental Association Chapters in the National Capital Region - Hernandez, Shaliza d.J; Javier, Ronilyne L. (Department of Community Dentistry, University of the Philippines Manila, 2016)
INTRODUCTION: To help address the alarming oral health status among Filipinos, the local chapters of PDA provide free dental services to the underserved members of the community. This prompted the researchers to determine how the PDA-NCR chapters conduct their dental missions.